2019
DOI: 10.3389/fimmu.2019.00863
|View full text |Cite
|
Sign up to set email alerts
|

DC Respond to Cognate T Cell Interaction in the Antigen-Challenged Lymph Node

Abstract: Dendritic cells (DC) are unrivaled in their potential to prime naive T cells by presenting antigen and providing costimulation. DC are furthermore believed to decode antigen context by virtue of pattern recognition receptors and to polarize T cells through cytokine secretion toward distinct effector functions. Diverse polarized T helper (T H ) cells have been explored in great detail. In contrast, studies of instructing DC have to date largely been restricted to in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 62 publications
(69 reference statements)
1
13
0
Order By: Relevance
“…Finally, our data show that upon cognate interaction psDC acquire an antiviral program and they are more protected. Those data are supported by a study where it is shown that this also happens in DC in vivo 270 . Even if after immune synapse many DC die, some of these postsynaptic Dendritic Cells activate a program that improves their performance 271 .…”
Section: Discussionsupporting
confidence: 68%
“…Finally, our data show that upon cognate interaction psDC acquire an antiviral program and they are more protected. Those data are supported by a study where it is shown that this also happens in DC in vivo 270 . Even if after immune synapse many DC die, some of these postsynaptic Dendritic Cells activate a program that improves their performance 271 .…”
Section: Discussionsupporting
confidence: 68%
“…Barry et al found that intratumorally stimulatory DCs play important roles in the stimulation of cytotoxic T cells and driving the immune responses against cancer (28). Additionally, DCs were found to play a central role in the regulation of the balance between CD8 T-cell immunity vs. tolerance to tumor antigens (29)(30)(31). Of the antigen-presenting cells, DCs are the most effective in the activation of naïve T cells and induce an immune memory response in cancer (32).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the expression levels of MHC II, CD86, CD80, and CD40 increased through TCDD stimulation. DCs trigger T cells through MHC II, CD86, CD80, and CD40 presentation and costimulation, subsequently directly activating T cells [ 21 ]. CD40 activation induced Fas-dependent apoptosis and NF-kappaB/AP-1 signaling in human intrahepatic biliary epithelial cells [ 22 ].…”
Section: Discussionmentioning
confidence: 99%